Development of hard X-ray dark-field microscope using full-field optics. (20th September 2016) - Takano, Hidekazu; Azuma, Hiroaki; Shimomura, Sho; Tsuji, Takuya; Tsusaka, Yoshiyuki; Kagoshima, Yasushi
Abstract: We develop a dark-field X-ray microscope using full-field optics based on a synchrotron beamline. Our setup consists of a condenser system and a microscope objective with an angular acceptance larger than that of the condenser. The condenser system is moved downstream from its regular position such that the focus of the condenser is behind the objective. The dark-field microscope optics are configured by excluding the converging beam from the condenser at the focal point. The image properties of the system are evaluated by observing and calculating a Siemens star test chart with 10 keV X-rays. Our setup allows easy switching to bright-field imaging.